Postoperative Hemostasis and Fibrinolysis in Patients Undergoing Cardiopulmonary Bypass with or without Aprotinin Therapy - Lu, He; Du Buit, Charles; Soria, Jeannette; Touchot, Bernard; Chollet, Bernard; Commin, Pierre L; Conseiller, Christian; Echter, Ernest; Soria, Claudine (Thrombosis and Haemostasis, 1994)
Intra- and postoperative blood loss during open heart surgery is reduced by approximately 50% when aprotinin, a potent inhibitor for plasmin and kallikrein, is administered during surgery. But whether aprotinin increases the risk of thrombotic complications remains controversial. The aim of this study was to evaluate the effects of aprotinin administration on coagulation and fibrinolysis during and after cardiopulmonary bypass (CPB). Thirty patients undergoing CPB were randomly assigned to two comparable groups for a double-blind study (16 patients receiving high-dose aprotinin, 14 patients receiving placebo). Patients’ plasma levels of ATM (thrombin-induced modified antithrombin III), FbDP (fibrin degradation products, D-Dimers), t-PA (tissue-type plasminogen activator) and PAI-1 (plasminogen activator inhibitor type 1) were measured at regular intervals. In both groups, ATM level increased during surgery (from less than 30 to 90-110 ng/ml) and returned to normal 24 h after surgery and remained unchanged thereafter. Aprotinin reduced this increase in ATM levels (p = 0.02 at 30 min after the start of CPB). The FbDP generated during surgery was greatly reduced in the aprotinin group (945 ng/ml) in comparison with the placebo group (1889 ng/ml, p = 0.004). After surgery, FbDP levels decreased in both groups with nadirs at 2nd day (placebo group: 940 ng/ml and aprotinin group: 865 ng/ml) indicating a hypo-fibrinolytic period. Then, the FbDP level in both groups started to increase up to the 9th day, in an identical manner. This postoperative hypofibrinolysis is related to the changes of t-PA and PAI-1 levels: immediately after surgery there was a 2’fold increase in t-PA level and a 4-5 fold increase in PAI-1 level in the two groups. During the following 24 h, t-PA levels decreased in both groups. In contrast, PAI-1 levels in the placebo group during the same time increased sharply to a maximum level (175.7 ng/ml). This further increase did not occur in the aprotinin group although it remained at a high level (79.2 ng/ml). The difference in the increase of PAI-1 between the 2 groups (value at 24 h minus preoperative value: Dl-Tl) was significantly different (p = 0.04). Then t-PA continued to decrease and PAI-1 began to decrease steadily. Total blood loss was significantly reduced by aprotinin therapy (3.06 ml/kg versus 5.86 ml/kg). The present study confirms the inhibitory effects of aprotinin on both fibrinolytic activity and blood coagulation activation during CPB, and reveals an hypofibrinolytic period that lasts 48 h after surgery in both aprotinin and placebo groups. This inhibition of fibrinolysis is apparently associated with high PAI-1 level. The data of this study also show that 2 days after aprotinin therapy, there is no prolonged effect of aprotinin on fibrinolysis. In addition, the lower level of PAI-1 in the aprotinin group after surgery might result from a protection of endothelial cells by aprotinin, suggesting an unexpected benefit of aprotinin therapy.